Identification of two cytotoxic T lymphocyte-recognized epitopes in the Ras protein (The Rockefeller University Press, 1993)
We have investigated the possibility of inducing cytotoxic T lymphocytes (CTL) to Ras containing a mutation at position 61 or to normal Ras, using recombinant vaccinia viruses expressing these proteins. CTL from C57Bl/10 mice immunized with vaccinia expressing mutant Ras showed specificity for the mutant Ras protein and recognition of normal Ras was inefficient. The opposite specificity was observed after immunization with vaccinia expressing normal Ras, since CTL isolated from these mice recognized normal Ras well and mutant Ras inefficiently. Levels of endogenous Ras expression were insufficient for lysis by these CTL. One CTL epitope mapped to amino acids 60-67 and residue 61 was critical for T cell recognition. CTL generated against mutant Ras protein recognized peptide 60-67 containing mutant residue 61, while anti-normal Ras CTL recognized the wild-type 60-67 sequence. A second epitope mapped to residues 152-159 of Ras and was recognized equally well by CTL raised to normal or mutant Ras. The murine data raise the possibility of exploiting Ras-specific CTL for targeted immunotherapy of certain human cancers.